Production of recycled paper reinforced cellulose nanofiber (CNF) - Muhamad Firdaus, Juhari; Atiqah, Mohd Shahabuddin; Nurhamizah Adlin, Abdul Halim; Khairatun Najwa, Mohd Amin (2021)
68 Million trees are cutdown every year (Pivnenko etal., 2014). Paper waste increasing from 15 to 35 Million tonnes over 10 years.